1998
DOI: 10.2307/3588000
|View full text |Cite
|
Sign up to set email alerts
|

"It's Always More Difficult Than You Plan and Imagine": Teachers' Perceived Difficulties in Introducing the Communicative Approach in South Korea

Abstract: Despite the widespread adoption of communicative language teaching (CLT) in ESL countries, research suggests that curricular innovations prompted by the adoption of CLT in EFL countries have generally been difficult. The literature on curriculum innovation suggests that teachers' understanding of an innovation is central to its success. A study of a group of South Korean secondary school English teachers' perceived difficulties in adopting CLT reveals that the difficulties have their source in the differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
393
4
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 436 publications
(439 citation statements)
references
References 49 publications
33
393
4
9
Order By: Relevance
“…Various research studies reported that instruction in EFL classrooms was still based on the traditional approach (Littlewood, 2007;Nunan, 2003;Savignon and Wang, 2003). The ideas of CLT are different from the educational values and traditions of many EFL settings (Burnaby & Sun, 1989;Li, 1998). In addition, situational factors such as large class sizes, test-oriented instruction, and students' low proficiency also influenced CLT practices.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…Various research studies reported that instruction in EFL classrooms was still based on the traditional approach (Littlewood, 2007;Nunan, 2003;Savignon and Wang, 2003). The ideas of CLT are different from the educational values and traditions of many EFL settings (Burnaby & Sun, 1989;Li, 1998). In addition, situational factors such as large class sizes, test-oriented instruction, and students' low proficiency also influenced CLT practices.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The implementation of CLT has encountered problems and resistance in EFL classrooms (Ellis, 1996;Li, 1998;Liao, 2000;Yu, 2001). Various research studies reported that instruction in EFL classrooms was still based on the traditional approach (Littlewood, 2007;Nunan, 2003;Savignon and Wang, 2003).…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 3 more Smart Citations